Evaluation of the system "quality of education" and its socio-economic impact: analogies with software testing - Artem Artyukhov; Iurii Volk; Nadiia Artyukhova; Roman Halenin; Liudmyla Batsenko (Academy of Cognitive and Natural Sciences, 2023)
This article has been retracted. Please see: Retraction of published article due to the author's proposal - 5 June 2023 The article is devoted to creating a reliable algorithm for testing the quality of the education system, determining the system's relationship with the goals of sustainable development, and the resolution of indicators of the socio-economic impact of the system. The substantiation of the application of analogies between testing software products and testing the dynamic system "quality of education" is presented. A type of relationship between the goal of sustainable development SDG 4 "Quality education" and other goals of sustainable development, particularly with SDG 8, "Decent work and economic growth" through the criteria for evaluating educational programs, is proposed. Based on the bibliometric analysis, the indicators of the socio-economic impact of the "quality of education" system are highlighted. The general algorithm for testing the design and the structural and logical diagram of the relationship between internal and external testing of the system are presented.